Mendamaikan Logika Normativitas dan Historisitas dalam Studi Agama - Nella Lucky (Farabi, 2016)
The dissent among the internal and external of religious communities essentially not because the divergence of religious concept. It appears because different methodology and logical thinking among the intellectuals that influence the people in vast dimensions. The differences of logical thingking will impact the different product of thought and religious activities. Among others is the different of normativity and historicity methods and logical thinking. Throughout the course of history, both logic collide each other. So the effort to integrate this both logic absolutely necessary for the advancement of development of religious studies in the future